2007
DOI: 10.1111/j.1469-8749.2007.00587.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased inflammatory markers are associated with early periventricular leukomalacia

Abstract: The aim of the study was to investigate whether inflammatory markers are associated with the occurrence of periventricular leukomalacia (PVL). Superoxide (O2‐) production of neutrophils and plasma antioxidative superoxide dismutase (SOD) activity in umbilical cord blood were studied. Participants were preterm infants with early PVL (n=6; three males, three females; mean birthweight 1458g [SD 517], range 620–2040g; mean gestational age 29.8wks [SD 2.9], range 27–34wks); and preterm control infants without PVL (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 15 publications
(19 reference statements)
3
11
0
Order By: Relevance
“…NOX1 is the major enzymatic mediator of superoxide anion generation in neutrophils (42). Increased expression of NOX1 by neonatal neutrophils is consistent with previous reports that in response to inflammatory stimuli, these cells produce greater amounts of superoxide anion relative to adult cells (43). Of note is our observation that constitutive expression of NOX1 was lower in neonatal relative to adult cells.…”
Section: Discussionsupporting
confidence: 91%
“…NOX1 is the major enzymatic mediator of superoxide anion generation in neutrophils (42). Increased expression of NOX1 by neonatal neutrophils is consistent with previous reports that in response to inflammatory stimuli, these cells produce greater amounts of superoxide anion relative to adult cells (43). Of note is our observation that constitutive expression of NOX1 was lower in neonatal relative to adult cells.…”
Section: Discussionsupporting
confidence: 91%
“…We also confirmed the several reports of a significant association between cPVL and chorioamnionitis [8, 9, 11, 14, 15]. The fact that only one cPVL baby had a positive blood culture within 3 days of birth supports the hypothesis that fetal inflammatory response syndrome is perfectly capable of causing brain damage even in the absence of bacteremia [32–34].…”
Section: Discussionsupporting
confidence: 90%
“…In a recent study, preterm infants with early WMD as detected by ultrasound and confirmed by MRI had higher cord blood concentrations of TNF-␣ and IL-1␤ (30). Both white and gray matter abnormalities detected by MRI in preterm infants have been associated with abnormal functional outcome (5).…”
Section: Discussionmentioning
confidence: 99%